A Comparative Study of the Gut Microbiota Associated With Immunoglobulin a Nephropathy and Membranous Nephropathy - Dong, Ruijuan; Bai, Ming; Zhao, Jin; Wang, Di; Ning, Xiaoxuan; Sun, Shiren (Frontiers in Cellular and Infection Microbiology, 2020)
The pathogenesis of immunoglobulin A nephropathy (IgAN) and membranous nephropathy (MN) is characterized by immune dysregulation, which is related to gut dysbiosis. The aim of the study was to compare the gut microbiota of patients with IgAN and MN versus healthy controls. We used 16S rDNA amplicon sequencing to investigate the bacterial communities of 44 patients with kidney biopsy-proven IgAN, 40 patients with kidney biopsy-proven MN, and 30 matched healthy controls (HC). The abundance of Escherichia-Shigella and Defluviitaleaceae_incertae_sedis were significantly higher in IgAN than in HC, whereas lower abundances were observed for Roseburia, Lachnospiraceae_unclassified, Clostridium_sensu_stricto_1, and Fusobacterium. Furthermore, the abundance of Escherichia-Shigella, Peptostreptococcaceae_incertae_sedis, Streptococcus, and Enterobacteriaceae_unclassified increased, while that of Lachnospira, Lachnospiraceae_unclassified, Clostridium_sensu_stricto_1, and Veillonella decreased in MN. The abundance of Megasphaera and Bilophila was higher, whereas that of Megamonas, Veillonella, Klebsiella, and Streptococcus was lower in patients with IgAN than in those with MN. Analysis of the correlations showed that in the IgAN group, Prevotella was positively correlated, while Klebsiella, Citrobacter, and Fusobacterium were negatively correlated with the level of serum albumin. Positive correlation also existed between Bilophila and Crescents in the Oxford classification of IgAN. In the MN group, negative correlation was observed between Escherichia-Shigella and proteinuria, Bacteroides and Klebsiella showed positive correlation with the MN stage. Patients with IgAN and MN exhibited gut microbial signatures distinct from healthy controls. Our study suggests the potential of gut microbiota as specific biomarker and contributor in the pathogenesis of IgAN and MN.